Obstetric outcome in primigravida with unengaged versus engaged fetal head at term - Sirisha, Vandana Sai; Chiniwar, Mahantappa A.; Menasinkai, Sharada B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Labour although a physiological process can present challenges to clinician and patient. Primigravida and nulliparae are obstetric high-risk group, especially the very young and the elderly, where pregnancy and labour must be supervised. The study was done to compare the maternal and fetal outcome in primigravida with unengaged and engaged head at term. Methods: A prospective study was done for a period of 18 months from June 2018 to December 2019 in Department of Obstetrics and Gynaecology Adichunchanagiri Institute of Medical Sciences and Research Center. 100 women with unengaged head at term (group A) and 100 women with engaged head at term (group B) as controls were selected. All the relevant data was filled in the partogram. Following observations were made, station of fetal head at the onset of labour, course of labour, duration of labour, any medical or surgical interventions or caesarean delivery. Data was analysed by SPSS 20.0 software and p value<0.05 was taken as statistically significant. Results: in group A 49% and 63% in group B had vaginal delivery. 17% of group A and 14% of group B had instrumental vaginal delivery. Caesarean delivery was 34% in group A and 23% in group B. The mean total duration of labour was 13.53 hours in group A and 9.73 hours in group B. P value was 0.000. Conclusions: Duration of labour was more in group A than group B. Proper supervision and timely intervention in cases with an unengaged head can have vaginal delivery.